The Impact of Fasting and Dietary Interventions on the Development and Treatment of Non-Hodgkin’s Lymphomas and Other Cancers - a review - Bilecki, Krzysztof; Cuper, Paulina; Jastrzębska, Ilona; Kozicz, Michał Andrzej; Gugulski, Hubert; Bado, Michał; Nowoświat, Patrycja; Goncerz, Michał (Quality in Sport, 2024)
Introduction: The present study investigated the role of fasting and diet in the development and treatment of cancers, with a focus on non-Hodgkin’s lymphomas. Dietary components and regimens have an impact on the risk of development of malignances as well as on the treatment of the disease. Cancerous subtypes react differently to various dietary compounds and regimes. Although not widely used- fasting can be valuable help in cancer treatment. In this article we show how diet modifications and restrictions can affect existing therapies. Aim of the study: By analyzing current literature, the study aimed to understand how various dietary components and regimens influence cancer risk and treatment efficacy. Methods: Extensive research was conducted using PubMed and Google Scholar. References from selected articles were included in the analysis. Results: Consuming high amount of fruits and vegetables, unsaturated fats and supplementing vitamin D can reduce the risk of malignancies, with red meat, dairy products and saturated fats intake increasing it. Fasting affects lipid, glucose, protein and neuroendocrine metabolism in the way that helps the treatment of cancers. It slows down tumor growth, reduces some symptoms and improves the effects of chemotherapy. Exploring this topic further could propagate suitable diets for cancer subtypes as well as popularize fasting, which is not yet a widely known adition to standard anti-cancer treatments.